1986
DOI: 10.1088/0022-3727/19/12/012
|View full text |Cite
|
Sign up to set email alerts
|

Density distribution of an electron plasma column in a Penning discharge

Abstract: A technique of determining the density distribution of an electron plasma column confined by non-uniform magnetic fields is presented. The non-uniform confining fields cause the electron density distribution to be non-uniform not only radially, but also axially. Calculations of the plasma shapes show that for a stable plasma mode the plasma surface follows a flux tube in some range of the z axis and gradually shrinks towards the ends. For the plasma whose surface follows a flux tube, the central density profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1992
1992

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In Ref. [2] we have shown that the electron Table I. A set of the parameters of the plasma columns whose radial projiles are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In Ref. [2] we have shown that the electron Table I. A set of the parameters of the plasma columns whose radial projiles are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%